Daerah Penangkapan Ikan Demersal dan Musim Perairan Bagian Selatan Pulau Gorom Kabupaten Seram Bagian Timur - Selfi Sangadji; Delly Matrutty (Universitas Pattimura, 2023)
The sea waters in the Southern part of Gorom Island are one of the waters that has the potential to be used as an economically important demersal fishing area. The aim of this research is to analyze and map demersal fish fishing grounds, seasons, and the distribution of fish types and sizes in the waters of the southern part of Gorom Island. Data analysis was carried out descriptively qualitatively, while specifically for fishing ground maps using Argis software. The results of the analysis show that there are three demersal fishing grounds spread across the waters of the southern part of Gorom Island, namely: